Salama's Post-Traumatic Stress Disorder in Zoulfa Katouh's As Long as the Lemon Trees Grow: Salama's Post-Traumatic Stress Disorder in Zoulfa Katouh's As Long as the Lemon Trees Grow - Marantika, Gresyane Johana; Litaay, Adeline Grace M (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
Abstract. This study aims to discuss the problem of post-traumatic stress disorder in the novel As Long as the Lemon Tree Grow by Zoulfa Katouh. This study is focused on the symptoms, causes, and effects of post-traumatic stress disorder experienced by the main character in the story. This study uses PTSD theory to analyze post-trauma Salama stress disorder. The research method applied in this study is qualitative, with the literary psychology approach. According to the results of the analysis, there are four symptoms of post-traumatic stress disorder experienced by Salam. The first is to avoid reminders of traumatic events, the second is a disturbing mind, the third is feeling anxious and on edge, and the last is the symptom of passion and reactive. The cause of Salama's experience of post-traumatic stress disorder is a terror incident and bomb explosion that occurred in the past that affected his family, and this incident occurred again when he worked in a hospital in Homs. The effects of post-traumatic stress disorder that Salama experienced first were sedative, emotional, and social anxiety. This can be seen in the feelings of greetings because of the dispute that occurs between Salam and the military soldiers. Therefore, it can be concluded that realistic anxiety occurs when there is fear close to danger. Keywords: PTSD, symptoms of PTSD, causes of PTSD, effects of PTSD